The pathology of the early and late stages of primary pulmonary hypertension. Issue 3 (September 1987) - Heath, D; Smith, P; Gosney, J; Mulcahy, D; Fox, K; Yacoub, M; Harris, P
Abstract : During the course of a case of primary pulmonary hypertension occurring in a 24 year old man lung tissue became available at heart-lung transplantation in 1986 and from a lung biopsy carried out in 1981. In 1986 the sections showed classic plexogenic pulmonary arteriopathy. In 1981 they revealed migration of myofibroblasts into the intima and lumen of pulmonary arteries and arterioles, the identification of the cells being confirmed by electron microscopy. During the five years that the pulmonary vascular pathology progressed to the formation of plexiform lesions there was an increase in the number of bronchiolar endocrine cells that were immunoreactive to bombesin and calcitonin. This study demonstrates that the classic pathogenesis of primary plexogenic pulmonary arteriopathy originates years earlier as a migration of cells of muscular pedigree from the media into the intima of the pulmonary arteries and arterioles.